Prediabetes Induces More Severe Acute COVID-19 Associated With IL-6 Production Without Worsening Long-Term Symptoms - Bonyek-Silva, Icaro; Cerqueira-Silva, Thiago; Nunes, Sara; Machado, Antônio Fernando Araújo; Cruz, Márcio Rivison Silva; Pereira, Blenda; Estrela, Leilane; Silva, Jéssica; Isis, Ananda; Barral, Aldina; Oliveira, Pablo Rafael Silveira; Khouri, Ricardo; et al. (Frontiers in Endocrinology, 2022)
Aims: Pre-existing conditions, such as age, hypertension, obesity, and diabetes, constitute known risk factors for severe COVID-19. However, the impact of prediabetes mellitus (PDM) on COVID-19 severity is less clear. This study aimed to evaluate the influence of PDM in the acute and long-term phases of COVID-19. Materials and methods: We compared inflammatory mediators, laboratory and clinical parameters and symptoms in COVID-19 patients with prediabetes (PDM) and without diabetes (NDM) during the acute phase of infection and at three months post-hospitalization. Results: Patients with PDM had longer hospital stays and required intensive care unit admission more frequently than NDM. Upon hospitalization, PDM patients exhibited higher serum levels of interleukin 6 (IL-6), which is related to reduced partial pressure of oxygen (PaO2) in arterial blood, oxygen saturation (SpO2) and increased COVID-19 severity. However, at three months after discharge, those with PDM did not exhibit significant alterations in laboratory parameters or residual symptoms; however, PDM was observed to influence the profile of reported symptoms. Conclusions: PDM seems to be associated with increased risk of severe COVID-19, as well as higher serum levels of IL-6, which may constitute a potential biomarker of severe COVID-19 risk in affected patients. Furthermore, while PDM correlated with more severe acute-phase COVID-19, no long-term worsening of sequelae was observed.